Use of Internal Endoconduits as an Adjunct to Endovascular Aneurysm Repair in the Setting of Challenging Aortoiliac Anatomy - Wu, Timothy (2009)
The combination of Trans-Atlantic Intersociety Consensus (TASC) D aortoiliac occlusive disease as well as a symptomatic abdominal aortic aneurysm (AAA) is not a common occurrence. Extensive calcified atherosclerotic disease, occlusions, and small iliofemoral segmental arteries make transfemoral access difficult, if not impossible, for endovascular aneurysm repair (EVAR) in these patients. We present a case in which “controlled rupture” of the external iliac artery with a covered stent allowed transfemoral delivery of an aortouni-iliac stent graft with a completion femoral-to-femoral bypass. The patient is a 60-year-old male with a 5.3 cm symptomatic infrarenal AAA and a history of one block right leg claudication. Preoperative computed tomography angiography revealed the patient to have occlusion of the right common iliac artery, extensive calcified stenoses of his aortoiliac segments, and a prohibitively small left external iliac artery, which measured 4.5 mm at its narrowest diameter. The patient, despite discussions concerning the suitability of his iliac arteries as conduits for the delivery of the stent graft, insisted on an endovascular approach to lessen his chances of postoperative sexual dysfunction as well as minimize his length of stay. Access was obtained through bilateral femoral artery cutdowns, and attempts at dilating the left external iliac artery using 16-French dilators were performed without success. An 8 mm × 5 cm covered self-expanding stent was deployed in the diseased 4.5 mm left external iliac artery, followed by angioplasty performed with an 8 mm noncompliant balloon to disrupt the vessel. This endoconduit now allowed accommodation of our 18-French introducer for the aortouni-iliac stent graft. The operation was completed with a femoral—femoral bypass. Flow to both hypogastric arteries was preserved. We believe use of such techniques will ultimately expand the number of patients eligible for EVAR and avoid devastating access-related complications.